2015
DOI: 10.1038/srep07844
|View full text |Cite
|
Sign up to set email alerts
|

Dual Conical Conducting Filament Model in Resistance Switching TiO2 Thin Films

Abstract: The resetting behaviors of Pt/TiO2/Pt resistive switching (RS) cell in unipolar RS operations were studied in detail through an experiment and by modeling. The experiment showed that the apparently highly arbitrary resetting current-voltage (I–V) curves could be grouped into three types: normal, delayed, and abnormal behaviors. A dual conical conducting filament (CF) model was conceived, and their electrothermal behaviors were analytically described from the heat-balance and charge-transport equations. The alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…The CFs generated via this mechanism have been proposed to have a conical structure, which has been observed in TiO 2 . 132, 239,240 This CF growth process is schematically shown in Fig. 14(a).…”
Section: What Happens In An Oxide During Unipolar Switching?mentioning
confidence: 99%
“…The CFs generated via this mechanism have been proposed to have a conical structure, which has been observed in TiO 2 . 132, 239,240 This CF growth process is schematically shown in Fig. 14(a).…”
Section: What Happens In An Oxide During Unipolar Switching?mentioning
confidence: 99%
“…FEM in COMSOL Multiphysics software has been utilized for the simulation. It has been assumed that the active switching layer in the device constitutes a 'dual conical conductive filament' made of oxygen vacancies in the oxide layer, as proposed by Kim et al [3]. It is a simplified geometry of the complex non-linear curvature of the actual filament, which utilizes discontinuous cone geometry, with different slopes for the two sections of the dual-cone.…”
Section: Device Simulationmentioning
confidence: 99%
“…A wide range of materials such as transition metal oxides (e.g. HfO 2 [2], TiO 2 [3], Al 2 O 3 [4], Ta 2 O 5 [5], ZnO [6], VO 2 [7], etc. ), perovskite oxides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported RS behavior in structures such as Pt/TiO 2 /Pt [8,14,15], but large fluctuations in the I-V sweep curves exist during the reset operations, which are one of the big hurdles that the RS memory has to overcome to become a viable device [12]. Recently, a model has been proposed to explain these large fluctuations [16], that might have their origin in the stochastic nature of the set processes during the repeated RS via the I-V sweeps.…”
Section: Introductionmentioning
confidence: 97%